Eva Österberg: Mentalities and Other Realities. Essays in Medieval and Early Modern Scandinavian History. (Lund Studies in International History 28, Lund University Press, 1991). 207 s. - Ingesman, Per (Historie/Jyske Samlinger, 1993)
-